Reconnoitring Decentralization Policy of Education in Indonesia - Maharina Desimaria; Amy Yayuk Sri Rahayu (STAI Hubbulwathan Duri, 2022)
Education decentralization is a form of independent policy given by the government to regions in managing any educational practices. With a decentralized system, regions have the authority to determine all policies related to education, whether in curriculum structure, financing, supervision etc. This study is a systematic literature review that scrutinizes the implementation of the decentralization policy of education in Indonesia. Using the concept of Materla et al. 's (2017) systematic literature review that comprises review planning, review conducting, and review report and dissemination, this study included fifteen articles garnered from the databases obtained from Google Scholar and Pro-Quest. For the analysis process, a content analysis was employed using good governance principles that promote democracy, observance of human rights, accountability, transparency, and greater efficiency and effectiveness of the public sector (Agere, 2000). The findings report that the published literature discussing educational decentralization in Indonesia improving the local governance environment mainly concerns three main foci: contributions to local economic performance and competitiveness, empowerment of educational outcomes, and improvement of local public services. This article also provides recommendations for future researchers.